Substitution of maize with sorghum and millets in traditional processing of Mahewu, a non-alcoholic fermented cereal beverage - Nsingo-Kudita, Sakile; Schoustra, Sijmen; Mubaiwa, Juliet; Smid, Eddy J.; Linnemann, Anita R. (Oxford University Press, 2024)
There is growing interest in Sub-Saharan Africa for substituting maize with climate-smart crops like sorghum and millets in local food processing. We conducted a survey to explore current variations in processing and consumption practices for Mahewu, a traditionally fermented cereal beverage from Zimbabwe. Processing involved cooking a cereal porridge, adding cereal flour or malt as a starter ingredient, and fermenting for 12–48 h. Ingredient availability was the main driver for porridge ingredient choice (42% of respondents) with the most preferred being maize (55% of respondents), pearl millet (22%) and sorghum (9%). Final product taste had the most influence on starter ingredient choice, with most respondents preferring pearl millet flour (23%), finger millet malt (22%), wheat flour (17%), and sorghum malt (13%). Our study proves that maize can be replaced with sorghum and millet in Mahewu processing, thus increasing the climate-resilience of future food systems, and demonstrates that traditional practices harbour clues for adapting current practices.